2013
DOI: 10.4236/ce.2013.47a1001
|View full text |Cite
|
Sign up to set email alerts
|

Using Mobile Devices for Teaching Realistic Mathematics in Kindergarten Education

Abstract: New ICT tools allow children to take advantage of new learning platforms as well aiding them effectively in attaining new knowledge through activities related to their immediate interests and real life scenarios. Nowadays, computers and digital applications are a part of the daily life of children. In kindergarten education, properly designed digital educational activities can become a very powerful educational tool for efficient and effective learning. The utilization of interactive activities may contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 145 publications
(75 citation statements)
references
References 50 publications
6
52
0
17
Order By: Relevance
“…Characteristics such as increased portability, functionality, various multimedia capabilities, social interactivity, personalization, etc. that enable the implementation of a broader range of teaching strategies, make tablets attractive from an educational perspective (Zaranis et al, 2013). The findings are consistent with various international studies which find that using tablets is beneficial in kindergarten as they require minimal training, eliminate the disadvantages of handling additional material and increase children's motivation to learn.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Characteristics such as increased portability, functionality, various multimedia capabilities, social interactivity, personalization, etc. that enable the implementation of a broader range of teaching strategies, make tablets attractive from an educational perspective (Zaranis et al, 2013). The findings are consistent with various international studies which find that using tablets is beneficial in kindergarten as they require minimal training, eliminate the disadvantages of handling additional material and increase children's motivation to learn.…”
Section: Discussionsupporting
confidence: 86%
“…For Kucirkova (2014) tablets have three novel features with the potential to make a positive difference in early education: iPads are portable and light-weight, they eliminate the need for separate input devices (such as mouse and keyboard) and thirdly, they are specifically designed to accommodate a number of apps, many of which have a child friendly intuitive design. Concerning the pedagogical use of tablets in early childhood education, recent studies have concluded that tablets may have the potential to act as a valuable tool for educational use, especially in learning mathematical concepts (Pitchford, 2014;Shuler, Levine, & Ree, 2012;Zaranis et al, 2013). The regular use of tablets brings about significant learning gains to young children in areas such as arithmetic, recognition of numbers and formation of digits (Chiong & Shuler, 2010).…”
Section: Ict and Teaching Mathematics Concepts In Early Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results agree with the results of other similar studies showing the positive outcomes of a computer-based model of teaching mathematical concepts (Dimakos & Zaranis, 2010;Howie & Blignaut, 2009;Starkey, Klein, & Wakeley, 2004;Papadakis et al, 2016b;Trouche & Drijvers 2010;Zaranis et al, 2013). Therefore, the fourth research question was also answered positively.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, studies have shown that computers support the development of certain skills in children's memory, problem solving, language and mathematics (Ihmedieh, 2010;Judge, 2005;Kroesbergen, Van de Rijt, & Van Luit, 2007;Walcott et al 2009;Zaranis, Kalogiannakis, & Papadakis, 2013). Indeed, ICT can play a key role in achieving the objectives of the kindergarten curriculum, if supported by appropriate software applications embedded in proper educational scenarios (Dwyer 2007;Fisher, Denning, Higgins, & Loveless, 2012;Lee, 2009;Zaranis, 2014).…”
Section: Introductionmentioning
confidence: 99%